EDUKASI MANAJEMEN KELUARGA YANG BERFOKUS PADA ”KESEHATAN KEUANGAN” BAGI KADER POSYANDU DESA SINDANGSARI PABUARAN SERANG BANTEN - Hidayati, Siti; Rahayu, Agneta Irma; Fauziah, Cut; Muktamiroh, Hikmah; Wahyuningsih, Sri; Perdana, Fachruddin; Abdullah, Rukman (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This Community Service Program aims to provide education about family management that focuses on "financial health" to cadres of the Posyandu village of Sindangsari Pabuaran, Banten. A participatory approach is applied to encourage participants to be able to understand and master basic knowledge of family management, financial literacy and increase their insight into traditional myths that are irrelevant to the conditions of the times and can be improved. This community service activity involved 23 posyandu cadres, the PkM team and students. Education begins with a pre-test and ends with a post test, to measure the increase in participants' knowledge before and after education. The results of the post test showed that some participants already had basic knowledge of financial management, but they still needed to be given more knowledge about family management. Social media still has a great influence on the lives of participants, so financial literacy is very important to be applied. Related to traditional myths that are irrelevant to today's conditions, this education succeeded in changing the understanding of participants so that they no longer believe in these myths